(untitled) (Medico Legal Update, 2021)
Background/Objectives: The purpose of this study was to identify the factors affecting romantic relationship satisfaction of university students. Method/Statistical analysis: This study was conducted with 187 students from four universities in cities and provinces nationwide. Data were collected from September to October 2019 using a self-administered questionnaire. Collected data were analyzed through the stepwise regression analysis using the SPSS statistics program. Findings: The final regression model showed that self-esteem, anxiety attachment, and avoidance attachment were significant predictors related to romantic relationship satisfaction in university students and explained 34.7% of the variance in romantic relationship satisfaction. Improvements/Applications: The university student period is a time to form an adult attachment, thereby preparing for a happy marriage in the future by increasing the romantic relationship satisfaction. Therefore, it is necessary to develop and apply the educational programs that can increase self-esteem and positive heterosexual relationship for university students.